Big Data in Accounting Informaton Systems - Meiryani,; Sudrajat, Jajat; Daud, Zaidi Mat; Amelda, Banon (International Journal of Psychosocial Rehabilitation, 2020)
company must utilize existing technology to advance and increase its competitive level with other similar companies. Accounting information systems are required to be able to adapt to technological progress. Accounting information systems use data to process a report that provides information related to financial data for the company. Big data is in principle the same as data that is collected and stored and then analyzed. Technological developments that drive the movement of data towards big data. Characteristics of data that are classified as big data will make processing difficult for humans. Machine learning and artificial intelligence technologies are used to carry out the process. In the accounting process, big data is useful as follows:(1) providing ease and speed of access to transaction data flow; (2) can increase the effectiveness and efficiency of physical document storage costs; (3) changes in forensic audit and accounting techniques. This research is a literature study by examining research texts in international and national journals and accounting development reports in Indonesia.